A new species of Paranerilla Jouin & Swedmark, 1965 (Annelida: Polychaeta) from Brazil - Mendes, Samuel Lucas da Silva Delgado; Rodrigues, Jaqueline Carvalho; Rizzo, Alexandra E. (European Journal of Taxonomy, 2024)
Nerillids are small marine annelids, once placed at the artificial group ‘Archiannelida’, which contained all families of the exclusively interstitial polychaetes. Nerillidae is the most species rich family among them, with 71 species grouped into 15 genera, and represents an important component of the interstitial fauna, occupying a wide bathymetric range. Despite its problematic placement among the ‘Archiannelida’ families, the group per se is considered monophyletic. Currently, only two species of Paranerilla are valid, both being reported from the northern hemisphere. It is presented herein as the first description of a species of Paranerilla from tropical waters, named as Paranerilla schiavettii sp. nov., which is also considered as a unique record by the presence of a modified acicular spine in noto- and neuropodia from chaetiger 3–7, not mentioned in its congeners descriptions. Hence, we also propose an emendation on the genus diagnosis to embrace the presence of acicular spines within Paranerilla. So, the presented information complements the current knowledge about the group’s taxonomy and expands its distribution to South Atlantic waters.